2003
DOI: 10.1002/tox.10096
|View full text |Cite
|
Sign up to set email alerts
|

The freshwater cyanobacterium Lyngbya aerugineo‐coerulea produces compounds toxic to mice and to mammalian and fish cells

Abstract: Despite a growing awareness of the presence of cyanobacterial toxins, knowledge about the ability of specific species to produce toxic compounds is still rather limited. It was the overall goal of the current work to investigate if probes derived from the freshwater species Lyngbya aerugineo-coerulea (Kutz.) Gomont, a cyanobacterium frequently found in southern Europe and not previously investigated for the presence of bioactive compounds, were capable of eliciting in vivo and in vitro toxicity. The cyanobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…They found that the sulphonate moiety in quinovose was important in inhibiting the polymerase activity 11 . However, the cyanobacteria Microcystis, Phormidium, and Lyngbya also produce a wide variety of toxins implicated in animal and human poisoning incidents 30,31 . To date, attention has focused on the cyanobacteria Spirulina which has been widely used as a protein source and food supplement and cultivated for mass production in several countries including Thailand.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the sulphonate moiety in quinovose was important in inhibiting the polymerase activity 11 . However, the cyanobacteria Microcystis, Phormidium, and Lyngbya also produce a wide variety of toxins implicated in animal and human poisoning incidents 30,31 . To date, attention has focused on the cyanobacteria Spirulina which has been widely used as a protein source and food supplement and cultivated for mass production in several countries including Thailand.…”
Section: Resultsmentioning
confidence: 99%
“…Primary cell cultures from mouse kidney and mouse skin fibroblasts were prepared as previously described [22]. In addition, two commercially available mammalian cell lines were used for the in vitro tests: A549 (human lung carcinoma, ATCC CCL-185) and 3T3 (mouse embryonic fibroblasts, ATCC CCL-92).…”
Section: In Vitro Cell Cultures and Exposure Conditionsmentioning
confidence: 99%
“…L. aerugineo-coerulea has been also defined as a potential producer of extracellular and intracellular toxic substances [22].…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotal evidence suggest some toxicity remains once L. majuscula has been dried, as witnessed by fishers reporting eye and respiratory irritation when removing cyanobacteria from nets (Dermison and Abal, 1999). Lyngbya aeruginosa-coerulea has been found to release substantial amounts of cytotoxic compounds into the surrounding medium, and these were probably not due to cell lysis as cytotoxic effects differed between cells and medium (Treneva et al, 2003).…”
Section: Presence Of Extracellular Toxins In Environmentmentioning
confidence: 99%
“…Similarly, microcystins have been found in Microcystis, Anabaena, Oscillatoria, and Nostoc species. Recently another member of the genus, Lyngbya aeruginosa-coerulea has been found to be both neuro-and hepato-toxic, although no microcystins or saxitoxins were present (Treneva et al, 2003). Presence of LA in L. wollei will possibly have public health implications with large numbers of freshwater bodies in Florida as well as other states in the USA have this organism present.…”
Section: Presence Of Toxins In Other Species Of Lyngbyamentioning
confidence: 99%